Rom og sted Religionsfaglige og interdisiplinære bidrag - Saether, Knut-Willy; Aschim, Anders (Kyrkjefag Profil, 2020)
"Within the humanities, the concepts space and place have been the subject of renewed interest as theoretical resources over the last years, inspired by recent developments within the social sciences, and in particular human geography. In this volume, an interdisciplinary team of Norwegian scholars explore the potential of this «spatial turn» for disciplines like religious studies, theology, philosophy and educational studies. The book is edited by Knut-Willy Sæther, professor, Volda University College and Anders Aschim, professor, Inland Norway University of Applied Sciences. "